Assessment of Groundwater Quality for Drinking Purpose in an Industrial Area, Dumai City, Riau, Indonesia. - Fitri Mairizki; Risti Putri Angga; Arief Yandra Putra (UIR PRESS, 2020)
Groundwater is the main water resource especially for daily water needs. Population growth and urbanization have increased demand for water while the availability of groundwater has decreased both in quality and quantity. Various human activities also produce industrial, agriculture and municipal waste that can pollute groundwater through leaching process. The purposes of this study are to determine the quality of groundwater around tofu industrial factory and its evaluation for drinking water based on Health Minister Regulation No.492/MENKES/PER/IV/2010 and Government Regulation No.82 2001.The temperature, pH, total dissolved solids (TDS) and electrical conductivity (EC) were measured by using YSI-Pro. Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) were measured based on SNI 06-6989.2.2009 test method and SNI 06-698.72.2009 test method, respectively. Physically, groundwater had temperature average 28,60C, TDS 243 mg/L and EC 396 µS/cm. Almost all groundwater were acidic with pH average 5,6 and did not meet the drinking water quality requirements. Groundwater had COD average 78 mg/L, BOD average 36 mg/L and it were classified into moderate-heavy pollution. It indicated that groundwater may have been contaminated by organic material from tofu industrial wastewater. Therefore, groundwater should not be used as a source of drinking water.